The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1063/1.2711280
|View full text |Cite
|
Sign up to set email alerts
|

Electrical voltage manipulation of ferromagnetic microdomain structures in a ferromagnetic/ferroelectric hybrid structure

Abstract: We report on electrical bias voltage manipulation of the magnetic domain structures of patterned ferromagnetic Fe dots on a ferroelectric BaTiO3 underlayer using a scanning probe microscope technique. Piezoresponse force microscopy is used to apply local electric field on the Fe dots/BaTiO3 hybrid structure and to map the ferroelectric domain structures simultaneously. Magnetic force microscope observation also demonstrates that the magnetic domain structures of the Fe dots significantly change with the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Most methods achieve this control by using external magnetic fields or spin-torque current effects. 10,34 To demonstrate the ability of our computational approach to simulate such hybrid systems, we have modeled a ferromagnetic/PE bilayer system. 32,33 However, single-phase multiferroic materials tend to possess low magnetostrictive strain constants and, therefore, a weak magnetic response to electric field.…”
Section: Hybrid Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most methods achieve this control by using external magnetic fields or spin-torque current effects. 10,34 To demonstrate the ability of our computational approach to simulate such hybrid systems, we have modeled a ferromagnetic/PE bilayer system. 32,33 However, single-phase multiferroic materials tend to possess low magnetostrictive strain constants and, therefore, a weak magnetic response to electric field.…”
Section: Hybrid Systemsmentioning
confidence: 99%
“…12,34 As the voltage is increased to +0.1 V, the maximum stress along the x-axis increases to 0.15 GPa. This domain structure is frequently observed in similar elements.…”
Section: Hybrid Systemsmentioning
confidence: 99%
“…However the application of its antiferromagnetism, instead of ferromagnetism, is still hard to accomplish. Furthermore, the coupling between ferromagnetic metal and ferroelectric oxide, named artificial multiferroics, has currently attracted much attention and actually provides more possibilities for functionality design [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The coupling between ferromagnetism and ferroelectricity is mediated by the magneto-elastic effect through the reversible electric-field-controlled strain variation [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The coupling between ferromagnetism and ferroelectricity is mediated by the magneto-elastic effect through the reversible electric-field-controlled strain variation [22][23][24][25][26]. The ferroelectric materials of BaTiO 3 (BTO) [32][33][34][35] and Pb(Zr x Ti x 1− )O 3 (PZT) [26][27][28][29][30][31] have been widely used in the previous studies. For example, Lahtinen et al reported on the coupling between ferromagnetic and ferroelectric domains in CoFe/BTO heterostructures [33].…”
Section: Introductionmentioning
confidence: 99%
“…9 On the other hand, control of the magnetic domains by an electric field was investigated by different authors. [12][13][14][15][16][17][18] For instance, Ni ferromagnetic thin films (100 nm) on PZT films (1.3 lm) were used to reveal, by magnetic force microscopy (MFM), a control of the magnetic domain by changing the voltage applied to the ferroelectric layer. 13 Chung et al observed also shape modifications of magnetic domains when a 78 kV/cm electric field was applied to the PZT layer.…”
mentioning
confidence: 99%